Pengaruh Pendekatan Deep Learning Terhadap Pembelajaran Gerak Lokomotor pada Mata Pelajaran Pendidikan Jasmani di Sekolah Dasar - Topan Samudra Hidayat; Ayi Suherman; Tedi Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of training treatment on improving student learning outcomes and to compare the effectiveness of conventional and experimental methods. The method used was a quasi-experimental design with a nonequivalent control group design. The population of this study consisted of students, with samples divided into conventional and experimental groups. Both groups were given a pretest to determine initial ability, then the experimental group received a specific treatment, while the conventional group used regular learning methods, and ended with a posttest. The results showed a significant improvement in both groups, as evidenced by a significance value (Sig. 2-tailed) of 0.000 (< 0.05). The mean difference in the conventional group was -2.200 and in the experimental group was -4.150, indicating that the experimental group showed greater improvement. Thus, the treatment provided was proven to be more effective in improving student learning outcomes. Keywords: Deep Learning, Elementary School, Locomotor Skills, Motor Skills, Physical Education